Participation in and frequency of delinquent behavior: A test for structural differences - Nagin, Daniel (Journal of quantitative criminology, 1990)
In this paper we address whether there are distinctive differences in the processes determining participation in offending vs frequency of offending. We develop a number of tests to examine not only whether the correlates of participation and frequency are similar but also whether the same underlying statistical model is consistent with the data on both these dimensions of a criminal career. The tests are applied using data from the first two waves of the National Youth Survey. While the findings are not without ambiguities, they do not support the idea that distinguishing among the dimensions of a criminal career is a fundamental requirement for conducting sound research on the causes of crime and delinquency.